American Society of Anesthesiologists' Status Association With Cost and Length of Stay in Lumbar Laminectomy and Fusion: Results From an Institutional Database. Issue 5 (1st March 2020) - Bronheim, Rachel S.; Caridi, John M.; Steinberger, Jeremy; Hunter, Samuel; Neifert, Sean N.; Deutsch, Brian C.; DeMaria, Samuel; Hermann, Luke; Gal, Jonathan S.
Abstract : Study Design: Retrospective cohort study. Objective: The objective of this study was to characterize the costs associated with American Society of Anesthesiologists (ASA) class, and to determine the extent to which ASA status is a predictor of increased cost and LOS following lumbar laminectomy and fusion (LLF). Summary of Background Data: Spinal fusion accounts for the highest hospital costs of any surgical procedure performed in the United States, and ASA (American Society of Anesthesiologists) status is a known risk factor for cost and length of stay (LOS) in the orthopedic literature. There is a paucity of literature that directly addresses the influence of ASA status on cost and LOS following LLF. Methods: This is a retrospective cohort study of an institutional database of patients undergoing single-level LLF at an academic tertiary care facility from 2006 to 2016. Univariate comparisons were made using χ 2 tests for categorical variables and t tests for continuous variables. Multivariate linear regression was utilized to estimate regression coefficients, and to determine whether ASA status is an independent risk factor for cost and LOS. Results: A total of 1849 patients met inclusion criteria. For every one-point increase in ASA score, intensive care unit (ICU) LOS increased by 0.518 days ( P  < 0.001), and hospital length of stay increased by 1.93 days ( P  < 0.001). For every one-point increase in ASA score, direct cost increased by $7474.62 ( P  < 0.001). Conclusion: ASA status is a predictor of hospital LOS, ICU LOS, and direct cost. Consideration of the ways in which ASA status contributes to increased cost and prolonged LOS can allow for more accurate reimbursement adjustment and more precise targeting of efficiency and cost effectiveness initiatives. Level of Evidence: 3 Abstract : There is little literature that addresses the influence of American Society of Anesthesiologists (ASA) status on cost and length of stay following spinal fusion. Utilizing an institutional database, this study finds ASA score is an independent predictor of hospital length of stay, intensive care unit length of stay, and direct cost.